Theoretical analysis of dynamic chemical imaging with lasers using high-order harmonic generation - Le, Van-Hoang; Le, Anh-Thu; Xie, Rui-Hua; Lin, C. D. (My University, 2007)
We report theoretical investigations of the tomographic procedure suggested by Itatani et al. [Nature (London) 432, 867 (2004)] for reconstructing highest occupied molecular orbitals (HOMOs) using high-order harmonic generation (HHG). Due to the limited range of harmonics from the plateau region, we found that even under the most favorable assumptions, it is still very difficult to obtain accurate HOMO wave functions using the tomographic procedure, but the symmetry of the HOMOs and the internuclear separation between the atoms can be accurately extracted, especially when lasers of longer wavelengths are used to generate the HHG. Since the tomographic procedure relies on approximating the continuum wave functions in the recombination process by plane waves, the method can no longer be applied upon the improvement of the theory. For future chemical imaging with lasers, we suggest that one may want to focus on how to extract the positions of atoms in molecules instead, by developing an iterative method such that the theoretically calculated macroscopic HHG spectra can best fit the experimental HHG data.